Quality Attributes of Cured and Smoked Chicken Legs Using Different Processing Methods : doi: 10.5958/2581-6616.2021.00007.4 - S., A.; R., A.; K, Sen; Fairoze, Nadeem; Muthukumar, M.; Naveena, B.M.; Reddy, G. V. Bhaskar (Journal of Meat Science, 2022)
Preliminary trials for processing cured and smoked chicken legs were conducted using variables like a method of  treatment (dipping, dry curing, injection, and tumbling) and brine solution at different concentrations and optimized  by evaluating the product by a sensory panel and calculating the residual nitrite content. The processing methods (T1- Injection and dipping (24 hours); T2- Injection and tumbling twice for 30 min with a gap of 20 min in between, and  T3- Injection, tumbling for 20 min and dipping for 12 h) were adopted for the development of cured and smoked  chicken legs and evaluated the quality of developed products. No significant differences in the pH of chicken legs are  observed. The shear force value is significantly lower (P
Keywords: Cured and smoked chicken legs; Dipping; Injection; Tumbling; Marination; Quality characteristics